2018
DOI: 10.3390/coatings8100331
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of the Friction Mechanism of Hydrogenated Diamond-Like Carbon Film in Air by Varying Sliding Velocity

Abstract: The purpose of the present work is to probe the friction mechanism of hydrogenated diamond-like carbon (H-DLC) film in air by varying sliding velocity (25-1000 mm/s). Friction tests of Al 2 O 3 ball against H-DLC film were conducted with a rotational ball-on-disk tribometer. As the sliding velocity increases, both the friction coefficient and the surface wear of H-DLC film decrease, reach the minimum values, and then increase in the high sliding velocity region. Based on the observed results, three main fricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Thus, its contribution to the sharp drop in friction during the running-in process can be ruled out. Similar phenomena were reported in other studies [31,32,33].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, its contribution to the sharp drop in friction during the running-in process can be ruled out. Similar phenomena were reported in other studies [31,32,33].…”
Section: Discussionsupporting
confidence: 92%
“…Comparisons of friction coefficient values have to be made with caution, since environmental and test conditions, especially humidity [43], temperature [44], sliding velocity [45], load [46] and material of the counter face [47,48], influence the absolute value of the friction coefficient [49]. Concentrating on literature values from near-identical experiments, values of 0.1 or somewhat below are commonly found for a-C:H films prepared by PSII [50], whereas values of 0.05 are usually only achieved when dopants are added [51].…”
Section: Discussionmentioning
confidence: 99%
“…During the running-in of the H-DLC film, either the graphitization of the strained material or the removal of the oxide layer may change the surface properties of the substrate [12]. However, Tambe and Bhushan [34] indicated that the graphitization of H-DLC film may not occur at low sliding speed (< 400 μm/s) in the nanoscale wear tests.…”
Section: Role Of the Oxide Layer Removal In The Runningin Processmentioning
confidence: 99%
“…As an unavoidable phenomenon for most as-fabricated mechanical parts during the initial operation, runningin alters the performance of the moving components and plays a crucial role at all size scales, from macroscale engines down to dynamic nano-devices [1][2][3][4][5][6][7][8]. Diamond-like carbon (DLC) film is one of the most promising materials for reducing energy consumption and CO2 emission since it is capable of achieving super-low friction for sliding parts [9][10][11][12]. Except for a few specially treated DLC films, such as those with a pre-existing highly graphitized surface [8,13], most kinds of DLC films must initially undergo a transition to lower the friction level.…”
Section: Introductionmentioning
confidence: 99%